Structural and biochemical insights into the degradation mechanism of chitosan by chitosanase OU01 - Lyu, Qianqian; Shi, Yanhong; Wang, Song; Yang, Yan; Han, Baoqin; Liu, Wanshun; Jones, David N.M.; Liu, Weizhi (Biochimica et biophysica acta, 2015)
A detailed knowledge about the degradation mechanism of chitosanase hydrolysis is critical for the design of novel enzymes to produce well-defined chito-oligosaccharide products. Through the combination of structural and biochemical analysis, we present new findings that provide novel insights into the degradation mechanism of chitosanase OU01. We have determined the crystal structure of Asp43/Ala mutant of OU01, and have trapped the hydrolyzed product of the reaction. This structure reveals the role of the general acid (Glu25) in catalysis. Two structural features about the mechanisms of the non-processive chitosanases are described for the first time. 1). Structural comparison reveals that the enzyme goes through an open–closed–open conformational transition upon substrate binding and product release; 2). polar residues constitute the substrate binding cleft. Additional site important for polymeric substrate recognition is identified and a three-step polymeric substrate recognition mechanism is proposed. Detailed substrate recognition mechanism is described for non-processive chitosanase for the first time. These findings provide new structural insights into the understanding of overall hydrolysis mechanism for non-processive chitosanase, and also will facilitate the design of new enzymes used for industrial purpose. •We found the general acid (Glu25) formed interaction with +1 subsite of substrate.•A novel, three-step mechanism of polymeric chitosan substrate binding is proposed.•Non-processive chitosanases go through an open–closed–open conformational transition.